Foreign students at Rovaniemi University of Applied Sciences - Melikhova, Marina (Rovaniemen ammattikorkeakoulu, 2012)
The main goals of the thesis were to study why foreign students are interested in studying at RAMK, their satisfaction with the university and channels for promoting RAMK abroad. Moreover, the employment situation among foreign students in Finland was examined. The interest in this topic has risen after my student exchange in 2010 in Spain. A quantitative research method was used in this study. The research was done among exchange students and international degree students by using an online questionnaire. The questionnaire included open-ended and close-ended questions. The theoretical part of the thesis describes the marketing research process, the methods of the marketing research, studying abroad, the Finnish culture and the employment situation in Finland. The practical part describes the findings of the study done among exchange and international degree students. The results of the study show that the foreign students come to study at RAMK because of the good location of the school, its interesting degree programmes and recommendations of their fellow students, friends and relatives. Most of the students were satisfied with their studies at RAMK. However, some of them would like to have more practical work and small changes in the study curriculum. According to the exchange students’ opinions, presentations, reports, banners, brochures and videos would be good channels to promote RAMK. These could be published on the Internet, for instance on YouTube or Facebook. International degree students consider Internet, newspapers, television and schools abroad are the best promotion channels for RAMK. It was also discovered that the unemployment rate among foreign graduate and undergraduate students is very high and serious steps should be undertaken to improve the situation.